Pemberdayaan Guru dalam Meningkatkan Prestasi Sekolah (Studi Pada SMAN 10 Tasikmalaya) - Yonandi, Yonandi (LPPM Universitas Bina Bangsa, 2022)
Based on the results of a preliminary study at SMAN 10 Tasikmalaya which was studied, there are still problems in the learning process, such as there are still teachers who have not prepared learning before teaching, teachers have not used varied learning strategies so that students feel bored and do not focus on participating in learning activities. The formulation of the problem in this study is: 1) How is the teacher empowerment program in improving school achievement? 2) What are the priorities of teacher empowerment programs in improving school achievement? 3) How is the implementation of teacher empowerment programs in improving school achievement? 4) How to control teacher empowerment programs in improving school achievement?; 5) What are the barriers to teacher empowerment programs in improving school achievement?; 6) How to overcome the obstacles of teacher empowerment programs in improving school achievement? In this study, descriptive and explanatory methods were used. In the research, the data source chosen was all teachers at SMAN 10 Tasikmalaya. The sampling technique uses census techniques so that all populations are sampled, namely 57 people. Based on the results of the study, it is known that 1) The Head of SMAN 10 Tasikmalaya in implementing the teacher empowerment program has sent teachers to take part in workshops, upgrades, and training at the sub-district, district, provincial, and even national levels as long as there is an opportunity. 2) The principal has priority in carrying out teacher empowerment programs, namely the existence of priority programs that can improve the ability of teachers so that school achievement increases, namely holding a work shop that is carried out to provide new insights to teachers; 3) The principal has implemented a teacher empowerment program to improve school achievement by including teachers in various MGMP programs and trainings organized by the religious affairs department. 4) The principal has controlled the teacher empowerment program in improving school achievement by carrying out supervision and supervision to improve and improve the quality of learning in the classroom which ultimately also has an impact on improving the quality of education. 5) Some of the obstacles faced by the principal to improve school achievement include: there are differences in the thinking ability of educators, education staff and students in understanding the vision and mission to produce educational personnel with strong and intelligent characteristics. 6) Efforts to overcome the obstacles faced by the principal to improve school achievement, including conducting continuous and systematic socialization so that teachers have the same perception of the existing vision and mission, planning work programs carefully and meticulously so as not to clash with existing rules